External validation of the N descriptor in the proposed tumour–node–metastasis subclassification for lung cancer: the crucial role of histological type, number of resected nodes and adjuvant therapy. (8th August 2020) - Chiappetta, Marco; Lococo, Filippo; Leuzzi, Giovanni; Sperduti, Isabella; Petracca-Ciavarella, Leonardo; Bria, Emilio; Mucilli, Felice; Filosso, Pier Luigi; Ratto, Giovanni Battista; Spaggiari, Lorenzo; Facciolo, Francesco; Margaritora, Stefano
Abstract : The 8th edition of the tumour–node–metastasis (TNM) staging system for lung cancer was proposed in 2016 [1]. Abstract: OBJECTIVES: Overlapping survival curves for N1b (multiple N1 stations), N2a2 (single N2 station + N1 involvement) and N2a1 (skip N2 metastasis) limit the current tumour–node–metastasis (TNM) node (N) subclassification for node involvement. We validated externally the proposed subclassification. METHODS: Clinical records from a multicentric database comprising 1036 patients with pulmonary adenocarcinoma (ADC) or squamous cell carcinoma with N1/N2 involvement who underwent, from January 2002 to December 2014, complete lung resections were retrospectively reviewed. Patients were categorized according to the 8th TNM N subclassification proposal. Histological type, number of resected nodes (#RN) and adjuvant therapy (ADJ) were considered limiting factors. RESULTS: No difference in the 5-year overall survival (-OS) was noted between N1b and N2a1 (49.6% vs 44.8%, P  = 0.72); instead, the 5-year-OS was significantly improved in patients with squamous cell carcinoma (63% in N1b vs 30.7% in N2a1, P  = 0.04). In patients with ADC, the 5-year-OS was better in those with N2a1 than with N1b (50.6% vs 37.5%, P  = 0.09). When we compared N1b with N2a2, the 5-year-OS was statistically significant (49.6% vs 32.8%, P  = 0.02); considering only patients with squamous cell carcinoma (63% vs 25.8%, P  = 0.003), #RN >10 (63.2% vs 35.3%, P  = 0.05) and without ADJ (56.4% vs 24.5%, P  = 0.02), the 5-year-OS was significantly different. Differences were not significant for ADC, #RN <10 and ADJ. Finally, the 5-year-OS was statistically significant when we compared N2a1 with N2a2 of the total cohort (44.8% vs 32.8%, P  = 0.04), in ADC (5-year-OS 50.6% vs 36.5%, P  = 0.04) and #RN >10 (5-year-OS 49.8% vs 32.1%, P  = 0.03) without ADJ. CONCLUSIONS: Histological type, ADJ and #RN are relevant prognostic factors in N + non-small-cell lung cancer. Considering these results, we may better interpret the prognosis prediction limits of the proposed 8th TNM subclassification for the N descriptor.